Prevalence of Antibiotic Resistant Bacteria among the Clinical Samples from Different Hospitals of Peshawar, Pakistan - Muhammad Uzair Khan, Abid Ali Khan, Shahzad Ahmad, Khalida Kousar, Salman Ahmed, Zahid Ullah Khan, Amir Atlas, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Majority of the microorganisms are responsible for causing diseases which can be fatal if left untreated. In Pakistan this might be very critical because of the misuse and/or improper use of antibiotics. Objective: The current study was designed to point out the challenges of antibiotic resistance in Peshawar Pakistan. Methods: A total of 100 samples, 25 each from blood, pus, skin, urine were collected from four different hospitals of Peshawar, Pakistan. The samples were grown on culture media after collection. Results: Out 100 samples, 46 samples showed growth on culture medium. Four main isolates namely Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia, and Pseudomonas aeruginosa. S. aureus and E. coli were found in all tested samples blood, pus, skin, urine. P. aeruginosa was found in pus and K. pneumonia in urine only. The identified strains were subjected to sensitivity testing against 7 different antibiotics i.e., ampicillin, piperacillin tazobactam, doxycycline, aztreonam, ciprofloxacin, levofloxacin and teicoplanin. Conclusion: All of the bacterial species were found resistant against the applied antibiotics except aztreonam. Keywords: Prevalence, antibiotics sensitivity, S. aureus, E. coli, K. pneumonia, P. aeruginosa